1999
DOI: 10.1136/adc.80.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Unnatural sudden infant death

Abstract: Aim-To identify features to help paediatricians diVerentiate between natural and unnatural infant deaths.Method-Clinical features of 81 children judged by criminal and family courts to have been killed by their parents were studied. Health and social service records, court documents, and records from meetings with parents, relatives, and social workers were studied. Results-Initially, 42 children had been certified as dying from sudden infant death syndrome (SIDS), and 29 were given another cause of natural de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
1
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(78 citation statements)
references
References 27 publications
3
71
1
3
Order By: Relevance
“…[131][132][133] However, on the basis of an in-depth review of recurrent sudden unexpected infant deaths among families that had experienced 1 SIDS death, Carpenter et al 134 calculated an 87% probability that a second SIDS death within a family would be of natural cause. Calculations of the proportion of SIDS deaths attributable to covert homicide range from 6% to 10%, and recurrence risks for SIDS within a family in which 1 infant previously died of SIDS range from 2% to 6%.…”
Section: Infanticide and Sids Recurrencementioning
confidence: 99%
“…[131][132][133] However, on the basis of an in-depth review of recurrent sudden unexpected infant deaths among families that had experienced 1 SIDS death, Carpenter et al 134 calculated an 87% probability that a second SIDS death within a family would be of natural cause. Calculations of the proportion of SIDS deaths attributable to covert homicide range from 6% to 10%, and recurrence risks for SIDS within a family in which 1 infant previously died of SIDS range from 2% to 6%.…”
Section: Infanticide and Sids Recurrencementioning
confidence: 99%
“…‹lk kez 1969 y›l›nda, "herhangi bir infant ya da küçük çocukta, hikayesi ile beklenmeyen, tüm postmortem incelemelerle ölüm nedeni aç›klanamayan ani ölüm" fleklinde tan›mland› (5,12). 1979 y›l›nda, "The ninth edition of the International Classification of Disease (ICD-9)'da "Sudden infant death syndrome-798."…”
Section: Tanimunclassified
“…Özellikle tekrarlayan bebek ölümlerinde, "Munchausen syndrome by proxy", öldürücü çocuk istismar› ve bo¤ulan bebekler de ak›lda tutulmal›d›r (12,14,50,62,63). Asfiktik ölümlerde görülen intratorasik petefliyal ve intraalveoler kanamalar, ABÖS olgular›nda da görülmek-tedir.…”
Section: Ayirici Tani Ve öNer‹lerunclassified
“…Recent literature has suggested that the index of suspicion for unnatural death should be higher, particularly in families in which an unexplained infant death has occurred previously. 34 More recent publications, however, provide some reassurance that a percentage of recurrent, unexplained infant deaths may be, in fact, natural. 35,36 Estimates of the incidence of infanticide among cases designated as SIDS range from less than 1% to 5%.…”
Section: Child Abuse Fatalities By Suffocationmentioning
confidence: 99%